PROFIL MANAJEMEN DIRI GURU SMP : STUDI KASUS PADA GURU SMP MATA PELAJARAN UJIAN NASIONAL SUB RAYON SEMARANG UTARA - Muhdi Muhdi; Ngurah Ayu Nyoman Murniati (JP3 (Jurnal Pendidikan dan Profesi Pendidik), 2015)
National Examination subjects often become subjects scourge for all parties concerned. Not only students but school administrators often feel such concerns. Selection of subject teachers in accordance with the needs and objectives of the school to be one example of the role of the teacher determines the success of the national exam. Therefore, efforts to improve teacher quality national examination subjects is needed. Independently self-development should become self-awareness. Support from stakeholders motivates teachers to always work and achievement.This study uses a quantitative descriptive design. Focus observed were junior high school teachers with national examination subjects in the area of North Semarang.Results of the study describe IX class teacher profile in the selected region. Triangulation of the results showed a very heavy burden on teachers and teacher influence self-management is concerned. This has an impact on the low self-development of teachers. Recommendations are given to schools and stakeholders in fostering professionalism IX classroom teachers independently as an effort to improve achievement and school quality.